Implementation of RESTful web-services as a platform for exchanging information between grid operators - Trindade, Rui Miguel Marques Pereira (2021)
This work addresses the information exchange between System Operator for opera tional planning purposes. These System Operators are responsible for the correct func tioning of their electrical grid. With the increasing usage of renewable energy sources the coordination and information exchange between system operators must be improved. Amid the several potential areas of coordination between System Operators (TSO and DSO) the focus of this work relied on information exchange concerning the three phase Short circuit currents at the interface buses between TSO and DSO In order to make this information exchange a web-service Architecture is proposed. The web-service Architecture used was the RESTful which needs to follow the European Union’s specifications of data exchange. A structure for the type of information to be exchanged between Service Operators was developed and mapped to the Portuguese case, the information that was exchanged was the values of Scc and Icc of a given electrical grid (Short Circuit Power, Short Circuit Current) during a 24 hour period. An API (application programming interface) was developed that retrieves the information from a given grid and allows the required calculation. To test the implementation of the solution developed, a IEEE 14 based grid was de veloped using profiles of generation and loads based on real case data from REN (Redes Energéticas Nacionais). To simulate a 24 hour scenario 24 different cases were developed and tested in order to get a profile of the evolution of Scc. As for the RESTful Server it was tested with the API’s output files to ensure the correct transmission of data between the API and the Server. The results obtained on both the API and the Server are positive and reflected the expected outcome. The information retrieved from the API is validated, its output is well structured and contains the necessary information for the data exchange. As for the Server, the tests made were successful in testing the performance and fidelity of the information exchange and all developed functionalities.